2020
DOI: 10.1097/ncc.0000000000000882
|View full text |Cite
|
Sign up to set email alerts
|

A Resilience Model for Patients With Colorectal Cancer

Abstract: Background: Patients with colorectal cancer (CRC) experience multiple symptoms.Resilience is a positive health outcome that can assist patients to face and adapt to their disease. Objective: The purpose of this study was to evaluate a proposed resilience model for patients with CRC. Methods: Patients (n = 416), who were given a diagnosis of stage Ι to III CRC within the past 5 years, were recruited from 2 medical centers in Northern Taiwan. Symptom Severity Scale, Fatigue Symptom Inventory, and Center for Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The significant association between most recent serum levels of PSA and cancer‐specific self‐efficacy and resilience are innovative findings in PCSs. An earlier study on other cancer patients found that higher cancer‐specific self‐efficacy (Liu et al, 2021) or higher self‐efficacy in terms of coping (Chou et al, 2022) are associated with higher psychological resilience. Therefore, when PCSs are taught self‐management, their self‐efficacy in self‐management should improve.…”
Section: Discussionmentioning
confidence: 99%
“…The significant association between most recent serum levels of PSA and cancer‐specific self‐efficacy and resilience are innovative findings in PCSs. An earlier study on other cancer patients found that higher cancer‐specific self‐efficacy (Liu et al, 2021) or higher self‐efficacy in terms of coping (Chou et al, 2022) are associated with higher psychological resilience. Therefore, when PCSs are taught self‐management, their self‐efficacy in self‐management should improve.…”
Section: Discussionmentioning
confidence: 99%
“…For nurses as the health professionals who have the most contact with patients (Jiang et al, 2017), understanding these features of resilience in adults with colorectal cancer could enable them to identify potential problems in patients' adaptation to their illness and thereby provide individualised support and facilitate patients' recovery. The need for nurses to evaluate and promote resilience in patients with colorectal cancer has also been highlighted in previous studies (Chou et al, 2022;El-Rahman Mohamed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study also confirmed that suicide resilience was negatively associated with depression. In terms of tumors, patients with higher resilience are more able to flexibly manage their responses to adversity, successfully adapt to distress, cope with stress, and improve health-related outcomes ( Ristevska-Dimitrovska et al, 2015 ; Chou et al, 2022 ). Suicide resilience is not a single factor but a series of factors (emotional stability, internal and external protection), which reflects the use of individual resources or abilities to regulate thoughts, feelings or attitudes about suicide ( Osman et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much research has shown a connection between suicide resilience and suicidal ideation, and suicide resilience apparently has a unique protective effect on the development of suicidal ideation ( Rutter et al, 2008 ; Fang et al, 2015 ; Dhingra et al, 2016 ). Moreover, studies discovered that cancer patients with high resilience tended to be less depressed ( Ristevska-Dimitrovska et al, 2015 ; Chou et al, 2022 ). However, low resilience may result in negative mental health indicators (e.g., depression) ( Hu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%